Physiological Responses of an Arctic Crustose Coralline Alga (Leptophytum foecundum) to Variations in Salinity - Muth, Arley F.; Esbaugh, Andrew J.; Dunton, Kenneth H. (Frontiers in Plant Science, 2020)
In the Beaufort Sea, Arctic crustose coralline algae (CCA) persist in an environment of high seasonal variability defined by naturally low pH ocean water and high magnitude freshwater pulses in the spring. The effects of salinity on the CCA Leptophytum foecundum were observed through a series of laboratory and field experiments in Stefansson Sound, Alaska. We found that that salinity (treatments of 10, 20 and 30), independent of pH, affected L. foecundum physiology based on measurements of three parameters: photosynthetic yield, pigmentation, and calcium carbonate dissolution. Our experimental results revealed that L. foecundum individuals in the 10-salinity treatment exhibited an obvious stress response while those in the 20 and 30-salinity treatments were not significantly different for three parameters. Reciprocal in situ transplants and recruitment patterns between areas dominated by CCA and areas where CCA were absent illustrated that inshore locations receiving large pulses of freshwater were not suitable for CCA persistence. Ultimately, spatially and temporally varying salinity regimes levels affected distribution of CCA in the nearshore Arctic. These results have implications for epilithic benthic community structure in subtidal areas near freshwater sources and highlight the importance of salinity in CCA physiology.